Failed induction of labor and associated factors among women undergoing induction of labor - Patil, Gayatri L.; Pujar, Tejaswi V.; Hombardi, Pooja; R., Veda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Induction of labor (IOL) is increasingly employed in modern obstetric care, yet carries a significant risk of failure, contributing to higher caesarean rates and associated maternal-neonatal morbidity. Identifying factors that influence IOL success is essential for individualized labor management. Methods: This prospective observational study was conducted over one year at a tertiary care center in Karnataka, India. A total of 504 women undergoing IOL at ≥37 weeks gestation were enrolled. The induction protocol included mifepristone followed by misoprostol and oxytocin augmentation. Primary outcome was failed induction, defined as failure to enter active labor or caesarean delivery for failed progress. Associations between maternal and obstetric variables and IOL failure were analyzed using chi-square tests. Results: Out of 504 women, 181 (35.9%) experienced failed induction. PROM was the strongest predictor of failure (81.9%), followed by unfavorable Bishop score <5 (70.8%), maternal age <20 years (76.3%) or >35 years (67.5%), BMI >25 (58.3%), and post-term pregnancy (71.42%). Primigravidity and birth weight >4 kg were also significant contributors. Most caesareans due to failed induction resulted in favorable neonatal outcomes, though a small proportion required NICU admission. Conclusions: Failed induction is prevalent in women with PROM, low Bishop scores, maternal age extremes, high BMI, and suspected macrosomia. Pre-induction risk stratification and cervical ripening optimization can enhance IOL success and reduce cesarean burden.